Glial cells as therapeutic targets in progressive multiple sclerosis. (3rd June 2019) - Wilbanks, Brandon; Maher, LJ; Rodriguez, Moses
ABSTRACT: Introduction : Multiple sclerosis is a serious demyelinating disease of the central nervous system (CNS) with treatments generally restricted to immunosuppression to reduce attack rate and for symptom management. Glial cells may be useful targets for future CNS regenerative therapies to reverse disease. Areas covered : In this review, the authors cover currently available multiple sclerosis treatments and examine potential upcoming therapies targeting glial cells. The potential for new therapeutic approaches in the treatment of progressive multiple sclerosis is examined. Expert opinion : Microglia, astrocytes, and oligodendrocytes are each promising targets for the disease-altering treatment of multiple sclerosis. Though challenging, the opportunities presented have great potential for CNS regeneration and further investigation of glial cells in therapy is warranted. Patient-specific combinatorial therapy targeting the three glial cell types is expected to be the future of MS treatment.